Dokdo BE-subalgebras and BE-filters of BE-algebras (European Journal of Pure and Applied Mathematics, 2022)
With the aim of applying the Dokdo structure to BE-algebra, the notions of (weak) Dokdo BE-subalgebra and Dokdo BE-filter are introduced, and their properties are investigated. The relationship between weak Dokdo BE-subalgebra, Dokdo BE-subalgebra and Dokdo BE-filter is established. The conditions under which Dokdo structure can be weak Dokdo BE-subalgebra and Dokdo BE-filter,and the condition under which weak Dokdo BE-subalgebra can be Dokdo BE-subalgebra are explored. Characterizations of Dokdo BE-filter are provided.
Keywords: Weak Dokdo BE-subalgebra; Dokdo BE-subalgebra